Conductivity and dielectric studies of Li2SnO3 - Nor, A.F.M.; Majid, Siti Rohana; Teo, L.P.; Buraidah, M.H. (Springer Verlag (Germany), 2012)
Lithium stannate (Li2SnO3) has been prepared by solution evaporation method. The precursor obtained is sintered at 800A degrees C for 5, 6, and 7 h, respectively. X-ray diffractogram confirmed that the sample obtained after sintering is Li2SnO3. The pelletized Li2SnO3 after heating at 500 A degrees C for 3 h is used for electrochemical impedance spectroscopy characterization. Impedance measurements have been carried out over frequency range from 50 Hz to 1 MHz and temperature range from 563 to 633 K. The conductivity-temperature relationship is Arrhenian. Several important parameters such as activation energy, ionic hopping frequency and its rate, carrier concentration term, mobile ion number density, ionic mobility, and diffusion coefficient have been determined. The characteristics of log conductivity and log ionic hopping rate against temperature for the system suggest that the conduction and ionic hopping processes are thermally activated. The values of activation energy for conduction and relaxation processes as well as activation enthalpy for ionic hopping are about the same.